Metapher der Person im juristischen Diskurs. - Szubert, Rafał (Glottodidactica, 2015)
The title of my paper could have suggested that I was going to address the metaphor of a person in the legal discourse as a type of scientific discourse in a broad sense of the term, i.e. beyond any individual accounts of it. In my article, I present the person metaphor as the constitutive term for the theory of artificial persons. The point of departure for my deliberations, in which I try to demonstrate the nature of metaphorical expressions used in building legal theories, is a statement by Paul Kirchhof, who demanded that metaphorical expressions be eradicated from positive (statutory) law. In my article, I ask whether the demand can also be applied to theoretical deliberations of lawyers on the nature of law.